1998
DOI: 10.1074/jbc.273.45.29745
|View full text |Cite
|
Sign up to set email alerts
|

The Tight Junction Protein ZO-1 Establishes a Link between the Transmembrane Protein Occludin and the Actin Cytoskeleton

Abstract: The tight junction protein ZO-1 belongs to a family of multidomain proteins known as the membrane-associated guanylate kinase homologs (MAGUKs). ZO-1 has been demonstrated to interact with the transmembrane protein occludin, a second tight junction-specific MAGUK, ZO-2, and F-actin, although the nature and functional significance of these interactions is poorly understood. To further elucidate the role of ZO-1 within the epithelial tight junction, we have introduced epitope-tagged fragments of ZO-1 into cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
955
2
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,241 publications
(1,012 citation statements)
references
References 74 publications
(71 reference statements)
32
955
2
6
Order By: Relevance
“…filaments of the cell cytoskeleton (Fanning et al, 1998). In this study, ZO-1 protein content was higher in pigs fed with the highest dose of mZnO compared with control and pZnO and this confirms the protective role of Zn from ZnO in preventing TNF-α and IFN-γ-mediated increase in para-cellular permeability and alteration of TJ functionality.…”
Section: Discussionsupporting
confidence: 81%
“…filaments of the cell cytoskeleton (Fanning et al, 1998). In this study, ZO-1 protein content was higher in pigs fed with the highest dose of mZnO compared with control and pZnO and this confirms the protective role of Zn from ZnO in preventing TNF-α and IFN-γ-mediated increase in para-cellular permeability and alteration of TJ functionality.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous experiments (Wu et al, 1996) have shown that HA /P rearranged ZO-1, which is localized beneath the cell membrane inside the cells and is a direct link between occludin and the F-actin cytoskeleton (Fanning et al, 1998). We therefore investigated whether HA /P can induce degradation of ZO-1 as well.…”
Section: Resultsmentioning
confidence: 95%
“…This is a function for which MAGUKs are extremely well adapted: mediating such protein-protein interactions [17]. Indeed, several MAGUKs have been found to bind to components of the cadherin-actin system [55][56][57][58][59] and it has also been suggested that they link the tight junction constituents, occludin and claudins, with actin filaments [39]. MAGI-1 itself has been shown to localise to tight and adherens junctions [28], where it interacts with the β-catenin-E-cadherin complex [26], with the synaptopodin and alphaactinin-4 actin binding proteins [28], and with the JAM4 cell adhesion protein [29].…”
Section: Discussionmentioning
confidence: 99%